Diagnostic Dilemma Associated with Rhinomaxillary Mucormycosis: A Case Report of a Non COVID-19 Patient - Sugandha Arya; Jyoti Beniwal; Vaibhav Thakkar; Sandeep Saurabh; Ashish Pillania; Archana Raina; Satya Prakash Giri (New Frontiers in Medicine and Medical Research Vol. 12, 2021)
Mucormycosis is a life-threatening, opportunistic infection which poses a diagnostic and therapeutic challenge for the scientific community. It is a disease of the diseased. Rhinocerebral form of mucormycosis is the most common form. Initial site of occurrence is usually nasal mucosa or palate and subsequently fungi spreads to surrounding areas causing wide-spread necrosis. This life threatening pathology still attains a high mortality rate if an early diagnosis is not achieved. Therefore, proper neuroimaging, specific diagnostic tests like culture and histopathology for the early diagnosis is considered a step of grave importance for the appropriate management of the patient.